Adaptive capacity and coping strategies of small-scale coastal fisheries to declining fish catches: Insights from Tanzanian communities. Issue 108 (June 2020) - Silas, Mathew O.; Mgeleka, Said S.; Polte, Patrick; Sköld, Mattias; Lindborg, Regina; de la Torre-Castro, Maricela; Gullström, Martin
Highlights: Long-term records and artisanal fishers congruently confirmed a substantial decline in fish landings in Tanzania. Overfishing, environmental changes and destruction of habitats were perceived the drivers of fish catch declines. Fishers adapt to declining fish stocks by changing their resource use behaviours. Most fishers mentioned they will continue fishing in the future even if the fish landings would be further reduced. Strategic policies should include fishers' perceptions to adapt and cope with ongoing climate- and environmental changes. Abstract: Small-scale fishing communities are expected to adapt to fish catch fluctuations linked to global environmental change. Notwithstanding, impacts from severe climate events and overexploitation of fisheries resources can compromise functions and resilience of ecosystems and associated species, and thereby jeopardize long-term population trend stability and fisheries productivity. To date, most assessments and vulnerability studies of fisheries-dependent populaces have focused on global, regional and national levels, while studies at village and community levels, where adaptive planning in the context of climate- and environmental changes is important, are less common. Based on data from official fishery records over a three-decadal period (1984–2016) and recent interviews with artisanal fishermen (319 fishers from eight communities) along the Tanzanian coast, we assessed small-scale fisheries with regard to ( i ) long-term trends in fishery landings, ( ii ) long-term alterations in fishing gear use, and ( iii ) fishers' perceptions on how they have been coping and adapting to fluctuating fish landings. We further investigated ( iv ) the adaptive capacity of a wide range of coastal villages by assessing the fishers' responses to an anticipated future scenario of a major (50 %) decline in landings from the current fisheries catch levels. The long-term trend records of fish landings showed a remarkable ∼50 % reduction in terms of both catch per vessel and catch per fisher from 1984 to 2016. According to the interviews, the majority of fishers (75 %) have changed fishing grounds from nearshore to offshore areas during the last decade, owing to a general perception that nearshore areas have suffered major reduction in fish stocks (due to overfishing and environmental changes related to extreme climate- or weather events), while offshore areas were considered still productive. The change in location of fishing grounds is probably a result of the clear switch in major gear type utilization from beach seine to ring net that occurred over the last decades. With a further progressive decline in fishery catches to a predictive level of 50 % of the current catch level, there is a general perception that artisanal fishers will continue fishing because alternative livelihoods (like crop farming, which employs more than 65 % of the population) have suffered similar negative impact. These findings highlight the need for building adaptive capacity in local coastal communities to develop alternative coping strategies for the impacts of climate- and environmental changes.